2021
DOI: 10.1093/jas/skab159
|View full text |Cite
|
Sign up to set email alerts
|

The influence of xylanase on the fermentability, digestibility, and physicochemical properties of insoluble corn-based fiber along the gastrointestinal tract of growing pigs

Abstract: In theory, supplementing xylanase in corn-based swine diets should improve nutrient and energy digestibility and fiber fermentability, but its efficacy is inconsistent. The experimental objective was to investigate the impact of xylanase on energy and nutrient digestibility, digesta viscosity, and fermentation when pigs are fed a diet high in insoluble fiber (>20% neutral detergent fiber; NDF) and given a 46-d dietary adaptation period. Three replicates of 20 growing gilts were blocked by initial body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Feeds with high soluble NSP cause an increase in the viscosity of digesta due to their high water-holding capacity [ 2 , 51 ]. However, arabinoxylans and β-glucans in feeds contain β-glycosidic linkages, requiring exogenous NSP-degrading enzymes for the degradation of these NSP fractions [ 52 , 53 ]. Recently, NSP-degrading enzymes have shown synergistic effects on the hydrolysis of NSP, effectively decreasing the digesta viscosity in the small intestine in relation to enhanced intestinal health and growth of nursery pigs [ 3 , 30 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feeds with high soluble NSP cause an increase in the viscosity of digesta due to their high water-holding capacity [ 2 , 51 ]. However, arabinoxylans and β-glucans in feeds contain β-glycosidic linkages, requiring exogenous NSP-degrading enzymes for the degradation of these NSP fractions [ 52 , 53 ]. Recently, NSP-degrading enzymes have shown synergistic effects on the hydrolysis of NSP, effectively decreasing the digesta viscosity in the small intestine in relation to enhanced intestinal health and growth of nursery pigs [ 3 , 30 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The supplementation of XG had a positive impact on intestinal immune response, intestinal morphology parameters, and growth of nursery pigs in this study. The reason for this may result from the positive modulation of microbiota in the jejunal mucosa by the release of oligosaccharides [68,74,75], as well as an increase in nutrient availability with a reduction of digesta viscosity [10,13,53].…”
Section: Discussionmentioning
confidence: 99%
“…The observed effects were due to the high amount of neutral-detergent fiber (NDF) in the diets resulting in decreased nutrient and energy digestibility, reduction in relative hindgut fermentation, impairment of pig performance and dilution of dietary energy, as explained by Petry et al . (2021).…”
Section: Df In Gestating and Lactating Sowsmentioning
confidence: 99%
“…A recent study in gilts receiving an HF diet based on corn bran (30% of inclusion) also showed a decrease in DM, CP, gross energy, and fiber digestibility accompanied by increased digesta viscosity and reduced cecal fermentation. The observed effects were due to the high amount of neutral-detergent fiber (NDF) in the diets resulting in decreased nutrient and energy digestibility, reduction in relative hindgut fermentation, impairment of pig performance and dilution of dietary energy, as explained by Petry et al (2021).…”
Section: Df Nutrient Digestibility and Metabolic Effects On Sowsmentioning
confidence: 99%
“…However, NSPs are also an important nutrient for monogastric animals, especially for gut bacteria fermentation, which depends on the NSP components. It has been reported that exogenous addition of non-starch polysaccharide degrading enzymes (especially xylanase, XYL) can degrade insoluble and large soluble polysaccharides in the diet to produce oligosaccharides [ 9 , 10 ], oligosaccharides can be well fermented by intestinal bacteria. In addition, xylo-oligosaccarides (XOS) with a degree of polymerization in the range of 2–6, were identified to improve intestinal health and stimulate immune responses in animals, acting in a prebiotic manner [ 11 ].…”
Section: Introductionmentioning
confidence: 99%